Neuromyelitis optica during pregnancy. A case report - Mayner-Tresol, Gabriel (2019)
Neuromyelitis optica is a demyelinating autoimmune inflammatory disorder that affects the spinal cord and the optic nerves. The disease mechanism consists in the production of immunoglobulin G antibodies, which mainly target the aquaporin-4 channel, thus initiating an inflammatory and demyelinating process in the hypothalamic regions. Prognosis is poor. It has a prominent female predominance. Many of these patients are in childbearing age and pregnancy seems to be a factor that worsens the disease. We present a case of neuromyelitis optica during pregnancy in a 41-year-old patient with 23 weeks of gestation who suffered from cutaneous hypersensitivity, acute visual decrease of her right eye together with pain in eye movements, paresthesia and bilateral neuropathic pain of the lower and upper limbs. Magnetic resonance imaging showed an increase in the optic nerve and spinal cord uptake from C2 to C6 and the patient tested positive for aquaporin-4 antibodies. The patient was treated effectively with corticosteroids.